2010
DOI: 10.1088/0957-0233/21/8/085302
|View full text |Cite
|
Sign up to set email alerts
|

Camera-based noncontact metrology for static/dynamic testing of flexible multibody systems

Abstract: Presented here is a camera-based noncontact measurement theory for static/dynamic testing of flexible multibody systems that undergo large rigid, elastic and/or plastic deformations. The procedure and equations for accurate estimation of system parameters (i.e. the location and focal length of each camera and the transformation matrix relating its image and object coordinate systems) using an L-frame with four retroreflective markers are described in detail. Moreover, a method for refinement of estimated syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…where S F 3 is the laser spot on the PSD at the fixed end, in {F}. It follows from ( 6) and (11) that…”
Section: Derivation Of Measurement Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…where S F 3 is the laser spot on the PSD at the fixed end, in {F}. It follows from ( 6) and (11) that…”
Section: Derivation Of Measurement Equationsmentioning
confidence: 99%
“…It is demonstrated that deflection of a flexible body can be measured by capturing and tracing the instantaneous coordinates of markers by multiple cameras and triangulation techniques [11]. This camera-based non-contact metrology for testing of flexible multibody systems, also requires a lens distortion model that accounts for optical distortions.…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, this task is to find the mapping from 3D light rays to 2D image pixels, or equivalently find a best model that fits those data. It is a classical problem and often a critical step towards many practical robotic vision applications including 3D modelling and measurement [1], robot navigation and camera-based motion analysis systems [2].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Scanning laser vibrometers and camera-based motion analysis systems are two recent prominent systems for full-field measurements. The measured data from such a system contain detailed dynamic characteristics of the measured structure, but the amount of data is often huge.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in full-field noncontact dynamic measurement technologies stimulate further advancement of dynamics-based damage inspection of large structures because fast and accurate measurements of time-varying operational deflection shapes (ODSs) are ready for engineering applications. [13][14][15][16] Scanning laser vibrometers and camera-based motion analysis systems are two recent prominent systems for full-field measurements. The measured data from such a system contain detailed dynamic characteristics of the measured structure, but the amount of data is often huge.…”
Section: Introductionmentioning
confidence: 99%